The Effect of Income and Consumption Expenditure on the Level of Welfare of Urban Communities in East Java - Wahyudi Cakraningrat; Fadiyah Salsabilah (Cahaya Abadi Publisher, 2026)
Community welfare is one of the main indicators of the success of economic development which is influenced by various factors, including income and consumption expenditure. This study aims to analyze the influence of income and consumption expenditure on the level of welfare of urban communities in East Java for the period 2016–2025. The study uses a quantitative approach with a multiple linear regression method. The data used are secondary data in the form of time series obtained from the Central Statistics Agency (BPS) of East Java for the period 2016–2025. Data analysis techniques include classical assumption tests, multiple linear regression analysis, partial tests (t-tests), simultaneous tests (F-tests), and coefficient of determination (R²) tests. The results of the study indicate that partially the income variable (Sig. = 0.257) and consumption expenditure (Sig. = 0.771) do not significantly influence the level of community welfare. However, simultaneously income and consumption expenditure have a significant effect on the level of community welfare with an F value of 11.576 and a significance of 0.006. The Adjusted R Square value of 0.702 indicates that 70.2% of the variation in the level of community welfare can be explained by these two variables, while 29.8% is influenced by other factors outside the research model. This study concludes that community welfare is not only influenced by individual income and consumption expenditure, but also by various other economic factors, so that policies are needed that can increase real income and maintain people's purchasing power in a sustainable manner.